2020
DOI: 10.1097/hjh.0000000000002617
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic blood pressure recovery associates with physical performance, frailty and number of falls in geriatric outpatients

Abstract: Objective: Blood pressure (BP) recovery after orthostatic hypotension might be important to prevent cerebral hypoperfusion episodes in older adults, and be related to better clinical outcome. The objective was to study the relationship between BP recovery and clinical outcome, that is physical and cognitive performance, frailty and falls, in geriatric outpatients. Methods: One hundred and sixty-eight geriatric outpatients underwent continuous (beat-to-beat) BP measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
8
1
1
Order By: Relevance
“…BP recovery between 1 and 3 min after standing up measured with a sphygmomanometer was not associated with physical performance or number of falls in a large population of geriatric outpatients. The present results point in a different direction than previous studies, which used continuous BP measurements and reported BP recovery between 30 and 60 s after standing up to be associated with impaired physical performance, frailty, and falls [9, 11]. Patients may be particularly vulnerable for inadequate BP recovery in this time window as cerebral autoregulation might not have reached its full capacity [19].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…BP recovery between 1 and 3 min after standing up measured with a sphygmomanometer was not associated with physical performance or number of falls in a large population of geriatric outpatients. The present results point in a different direction than previous studies, which used continuous BP measurements and reported BP recovery between 30 and 60 s after standing up to be associated with impaired physical performance, frailty, and falls [9, 11]. Patients may be particularly vulnerable for inadequate BP recovery in this time window as cerebral autoregulation might not have reached its full capacity [19].…”
Section: Discussioncontrasting
confidence: 72%
“…Previous studies used a number of different BP recovery measures derived from continuous (beat-to-beat) BP measurements during and after standing up and found a lower BP recovery to be associated with physical performance, frailty, falls, and cognitive decline [8-11] but not with mortality [12-14]. However, continuous BP measurements are most often not available in clinical practice, in contrast to intermittent (sphygmomanometer) BP measurements.…”
Section: Introductionmentioning
confidence: 99%
“…These results extend our previous population-based work on probable sarcopenia [ 16 ] and, to the best of our knowledge, show for the first time an association between confirmed sarcopenia and delayed BP recovery using continuous non-invasive orthostatic haemodynamic measurements. Findings are clinically important as even in the absence of OH at 30 s, delayed BP recovery in the early post-standing phase can contribute to reduced cerebral perfusion and increase the risk of falls and syncope [ 8 , 28 , 29 ], which in turn can lead to fractures, hospital admissions, loss of functional independence, and risk of institutionalisation [ 9 , 30 ]. Although sarcopenia can directly lead to falls [ 31 ], our results suggest the existence of an indirect mechanism whereby sarcopenia could also contribute to falls by impairing early post-standing BP recovery.…”
Section: Discussionmentioning
confidence: 99%
“…57 Substantially more evidence comes from population-based studies on classic orthostatic hypotension and delayed blood pressure recovery patterns measured with traditional upper arm sphygmomanometers. Multiple large, prospective cohort studies of community-dwelling adults have shown that both delayed blood pressure recovery and classic orthostatic hypotension are associated with future risk of adverse health outcomes, including frailty, 47,58 falls, 5,20,21,47,58-61 frac tures, 41,59,62 syncope, 41 cognitive decline and demen tia, 61,63,64 depression, 65 stroke, 63,64,66,67 cardiovas cular disease, 66,68 and early death. 4,5,41,69 One study showed that early orthostatic hypotension (applying classic ortho static hypotension criteria within 1 min of standing) was more strongly related to individual long-term risks than later orthostatic hypotension (applying criteria in the 1-3 min range).…”
Section: Prognosis Of Orthostatic Hypotensionmentioning
confidence: 99%